2020
DOI: 10.1007/s12187-020-09788-8
|View full text |Cite
|
Sign up to set email alerts
|

A Global Decline in Adolescents’ Subjective Well-Being: a Comparative Study Exploring Patterns of Change in the Life Satisfaction of 15-Year-Old Students in 46 Countries

Abstract: There is a growing body of research that demonstrates declines in subjective well-being and increases in mental health problems among children and young people in recent decades. However, there is little comparative research examining changes in adolescents’ life satisfaction (LS) across a large number of countries, and critically, how this differs across sociodemographic groups. This study addresses this question by investigating changes in the LS of 15-year-old students between 2015 and 2018, with particular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 29 publications
9
49
3
Order By: Relevance
“…However, this model has failed to improve interventions in clinical psychology (Johnsen and Friborg, 2015 ; Ljótsson et al, 2017 ; Jones et al, 2019 ) and there are few reasons to believe its impact on positive psychology would be any different. Standing still also seems unwise, because despite decades of effort designed to promote well-being, there is no clear evidence that well-being is increasing in the world (Easterlin and Angelescu, 2009 ; Richter et al, 2019 ; Marquez and Long, 2021 ). A alternative approach is needed.…”
mentioning
confidence: 99%
“…However, this model has failed to improve interventions in clinical psychology (Johnsen and Friborg, 2015 ; Ljótsson et al, 2017 ; Jones et al, 2019 ) and there are few reasons to believe its impact on positive psychology would be any different. Standing still also seems unwise, because despite decades of effort designed to promote well-being, there is no clear evidence that well-being is increasing in the world (Easterlin and Angelescu, 2009 ; Richter et al, 2019 ; Marquez and Long, 2021 ). A alternative approach is needed.…”
mentioning
confidence: 99%
“…A few recent international comparative studies have explored declining levels of subjective well-being. For example, Marquez and Long (2020) identified a global decline in the LS of 15-year-old adolescents during the period 2015-2018, observed in 39 out of 46 countries studied. Importantly, despite significant cross-country variation, the study found that this decline was particularly accentuated among girls, as well as among adolescents of higher socio-economic status.…”
Section: Cross-country Variation In Population-level Declines In Adol...mentioning
confidence: 99%
“…There is an increasing body of research reporting population-level declines in subjective well-being and an increases in mental health problems among children and young people -particularly among females-observed over the last two decades in multiple countries (Curtin et al, 2016;Kim & Hagquist, 2018;Marquez & Long, 2020;Mishina et al, 2018;Mojtabai et al, 2016;The Children's Society, 2020;Twenge et al, 2017Twenge et al, , 2018. The present study investigates factors associated with population-level declines in 15-year-old adolescents' subjective well-being -more specifically, overall life satisfaction (LS)-with a focus on differences across gender and countries.…”
Section: Introductionmentioning
confidence: 99%
“…Such programming is timely as studies record global increases in youth depression, anxiety, and suicidality (Lai et al, 2018;Lawrence et al, 2015;Twenge et al, 2019;World Health Organization, 2017). Likewise, a study using the Programme for International Student Assessment (PISA) data for the years 2015 and 2018 found that, of 46 countries, of which the United Arab Emirates (UAE) was one, the average life satisfaction of 15 year olds in 39 nations had declined, particularly for females and students of higher socioeconomic classes (Marquez & Long, 2020).…”
Section: Using Positive Psychology Interventions (In a Pandemic)mentioning
confidence: 99%